Congenital heart disease at Laos Children's Hospital: Two year experience. Issue 3 (26th January 2017) - Hwang, In‐Chang; Sisavanh, Malouny; Billamay, Somxay; Phangmanixay, Sommanikhone; Oudavong, Bounleua; Kang, Jeehoon; Kwon, Bo Sang; Kim, Gi Beom; Bae, Eun Jung; Noh, Chung Il; Choi, Jung Yun
Abstract: Background: Management of congenital heart disease (CHD) in developing countries is challenging because of limited access to health‐care facilities and socioeconomic limitations. The aim of this study was to describe the recent experience with CHD at Children's Hospital, Vientiane, Laos, the only pediatric referral hospital in the country. Methods: From July 2013 to November 2015, 1009 echocardiograms were carried out in 797 individuals who visited Children's Hospital, in whom CHD was identified in 213. Demographic characteristics, echocardiography and age at first CHD diagnosis on echocardiogram were compared by residential area. Results: Among the 213 patients, the most frequent anomalies, in descending order, were ventricular septal defect, atrial septal defect, patent ductus arteriosus, and tetralogy of Fallot. Moderate or severe CHD requiring surgery or intervention was detected in 137 patients; median age at initial diagnosis was 6.0 months (IQR, 1.5–29.8). Among those with moderate or severe CHD, 89 patients were from rural areas and 48 from the capital area. The proportion of patients from rural areas older than 1 and 3 years at diagnosis was 46.1% and 32.6%, respectively. In contrast, patients from the capital area were diagnosed at a significantly earlier age: 16.7% at age >1 year and 6.2% at age >3 years (both P < 0.001 vs rural areas). Conclusions: Diagnosis of CHD requiring surgery is delayed in Laos, especially in rural areas. Better education and training of local medical staff, and greater access to medical advice are required to improve CHD care in Laos.